Trabalhadoras do sexo e profissionais da saúde: percepções sobre os processos educativos relacionados à saúde presentes no trabalho sexual - Ferreira, Flávia do Carmo (2006)
This work is focused on analising the similarities and differences of the perceptions of sex workers and public health system workers about the educative processes that is within sex work related to the sex workers health. We aim to examinate, in the point of view of both social groups, how the sex worker educates herself and others of her own class exchanging informations in the work group, with the client and with health worker seeking their perceptions about the processes which the sex worker teaches and/or learns health related knowledges, values or attitudes. We will also aim the relationship between health and sex work. This research is based on common sense definition according to Paulo Freire. It has been done with the support of the research methodology related with the participation of sex workers in interviews. Interviews are also done with health workers. We aim to contribute to destroy the stereotypes that keeps the prejudiced image of sex workers and also to help on contructing health politics that take this social group in a citizenship perpective.